Pericytes in the eye - Pfister, Frederick; Przybyt, Ewa; Harmsen, Martin C.; Hammes, Hans-Peter (Pflügers Archiv, 2013)
Pericytes in the retina differ from pericytes in many other organs by their high density and their cooperative role in the neurovascular unit. Their diverse ontogeny and the fact that not one pericyte marker identifies the entire population suggest also functional plurality in the retina, including invading cells of mesenchymal origin. Further, to establish factors determining pericyte recruitment, modifiers of pericyte adhesion and homeostasis, such as notch-3 and angptl-4, have been recently identified, expanding the understanding of pericyte function in the retina. Also, the role of pericytes as part of the neurovascular unit has been appreciated, given that the neuroglia determines pericyte survival and motility under disease conditions. Pericyte dropout is not unique in the diabetic retina, and non-diabetic animal models may prove useful in the search for mechanisms involved in disease-associated dysfunction of the neurovascular unit.
Gesehen am 22.03.2022